Electing to Do Women's Work? Gendered Divisions of Labor in U.K. Select Committees, 1979–2016. Issue 4 (December 2021) - Goodwin, Mark; Holden Bates, Stephen; McKay, Stephen
Abstract: Where female representatives are located within legislatures and what they do matters for the substantive representation of women. Previous scholarship has found that female parliamentary committee members participate differently than their male counterparts in relation to both policy area and status of positions held. Here, we draw on an original time-series data set ( n = 9, 767) to analyze the U.K. select committee system. We test for the impact of four variables previously found to be important in explaining changes in gendered divisions of labor: the system of appointment/election, the proportion of female representatives in the legislature, sharp increases in the number of female representatives, and changes in government from right-wing parties to left-wing parties. We find that horizontal and vertical divisions of labor persist over time and that membership patterns in the United Kingdom mainly correspond to those found elsewhere. Moreover, there is little evidence that any of the four variables have systematically affected membership patterns.